Progress in cryptology -- AFRICACRYPT 2017 : 9th International Conference on Cryptology in Africa, Dakar, Senegal, May 24-26, 2017, Proceedings /: 9th International Conference on Cryptology in Africa, Dakar, Senegal, May 24-26, 2017, Proceedings. (2017) - Unknown
No abstract available